Hellere være arving i Danmark end i Spanien: inddragelse af kulturspecifika i bilinguale fagordbøger - Sørensen, Rita (Nordiske Studier i Leksikografi, 1997)
Subject-:fields as leagal language, economics and politics are very culture-bound fields, as history and tradition here play an important role. This means that almost all bilingual dictionaries contain lemmata which are so culture-specific as to have no equivalent in the target language. In other cases the lemmata may be translated by way of lexical items that are "different" but which perform the same functions in the target language. In order to translate these lemmata the user needs information. How can this information be included in the dictionary?